Penguatan Implementasi Kurikulum Merdeka Melalui Pelatihan KOSP di Sekolah Indonesia Kuala Lumpur Malaysia - Hazin, Mufarrihul; Hariyati, Nunuk; Khamidi, Amrozi; Setiawan, Aditya Chandra (PT. Cahya Edupreneur Indonesia, 2023)
In the context of the Independent Curriculum, the Educational Unit Operational Curriculum (KOSP) aims to facilitate educational units in implementing competency development-based education which prioritizes developing students' abilities in a dynamic, complex and systematic manner. The aim of the service is to facilitate the preparation of KOSP at the Indonesian School, Kuala Lumpur, Malaysia. The method for implementing service in training for preparing operational curricula in Education Units (KOSP) is using the Goad model, (1982: 11) through several stages whose training cycle consists of: Analysis of training needs, Design of training approaches, Development of training materials, Implementation of training, and Evaluation and training updates. The results of service in the form of training show that; (1) needs analysis was extracted from school principals and teachers at SIKL and resulted in an urgent need for the development of KOSP to be implemented. (2) the training design is designed comprehensively; starting from pre-training, post-training, (3) The material developed consists of theory and practice which includes basic concepts, principles, components and steps for preparing KOSP. (4) the implementation of the training is guided by experienced resource persons and facilitators using adequate methods and media. (5) the evaluation used measures the quality of the material, sources and methods used and the results are very good and satisfactory. Future recommendations are to always improve the quality and strengthen the implementation of the Merdeka Curriculum in the SIKL Malaysia.